Microstructure and mechanical properties of CxHf0.25NbTaW0.5 refractory high-entropy alloys at room and high temperatures. (20th January 2022) - Wu, Shiyu; Qiao, Dongxu; Zhang, Haitao; Miao, Junwei; Zhao, Hongliang; Wang, Jun; Lu, Yiping; Wang, Tongmin; Li, Tingju
Highlights: A novel dual-phase NbTaW0.5 Hf0.25 Cx refractory high entropy alloys were designed and prepared. The C-added refractory high entropy alloys remain 1300 MPa with decent ductility of 30% at room temperature. The NbTaW0.5 Hf0.25 C0.25 alloy can remain ultra-high yield strength of 792 MPa and 749 MPa at 1473 K and 1673 K, respectively, exceeding all currently reported RHEAs. The mechanism of carbides on thermal deformation behavior was discussed. Abstract: The microstructure and mechanical properties of as-cast and isothermally annealed Cx Hf0.25 NbTaW0.5 ( x =0, 0.05, 0.15, 0.25) refractory high-entropy alloys (RHEAs) were studied. Both the as-cast and annealed RHEAs consisted of disordered body-centered cubic solid solution phase and metal carbide (MC) phase with a face-centered cubic crystal structure (Fm-3m space group). The primary carbides were enriched with Hf and C elements and tended to form lamellar eutectic-like microstructure in the interdendrites. The lamellar eutectic-like structure in the interdendrites would be formed from the decomposition of sub-carbide M2 C under the influence of Hf element. After isothermal annealing, slatted carbides were precipitated on the matrix, and the distribution became more uniform with high C content. The formation of carbides strongly influenced the mechanical properties both at room and high temperatures. The yield strength values of C0.25 Hf0.25 NbTaW0.5 RHEA at 1473 and 1673 K were 792 and 749 MPa, respectively. The result had exceeded the high temperature mechanical properties of currently known RHEAs. Moreover, this RHEA exhibited high-temperature performance stability and excellent plasticity, exceeding 30 and 50% at room and elevated temperatures (above 1273 K), respectively. During thermal deformation, carbon-containing RHEAs obtained more severe work hardening than that of ACH0 RHEAs, and required greater dynamic recrystallization to achieve the dynamic equilibrium. Graphical abstract: Image, graphical abstract